Investigation of Grain Radius Dependence of Sensitivity for Porous Thin Film Semiconducting Metal Oxide Gas Sensor - Yuan, Zhenyu; Zhang, Shouwen; Meng, Fanli; Zhang, Hua; Zuo, Kaiyuan (IEEE sensors journal, 2020)
In this paper, a new diffusion-reaction equation was formulated to research the influences of grain radius on the transients of gas transport and gas sensitivity for porous thin film medium semiconducting metal oxide gas sensor, based on the phenomenon that a target gas diffuses in the sensing film via Knudsen diffusion and reacts with adsorbed oxygen on the pore surfaces following Langmuir adsorption. In order to describe gas transport inside the sensing film, the equation has been solved numerically under unsteady-state conditions. When the gas concentration reached a steady state, the relationship between gas concentration and film depth was formulated using data fitting method to investigate the influences of grain radius on gas sensitivity, according to the linear relation between the sheet conductance of the sensing film and the gas concentration at the corresponding depth, and the reality that the conductance of the entire film is an integration of sheet conductance over the whole range of the film from the surface to the substrate.